Bomb blast injuries: an exploration of patient characteristics and outcome using Pakistan National Emergency Departments Surveillance (Pak-NEDS) data. Issue 2 (December 2015) - Khan, Irum; Khan, Nadeem; Naeem, Rubaba; Kerai, Salima; Allen, Kate; Zia, Nukhba; Shahbaz, Sana; Afridi, Shiraz; Siddiqui, Emaduddin; Khan, Uzma; Hyder, Adnan; Razzak, Junaid
Abstract Background Bomb blast injuries result in premature deaths and burdening of healthcare systems. The objective of this study was to explore the characteristics and outcome of patients presenting to the emergency departments in Pakistan with bomb blast injuries. Methods Active surveillance was conducted in seven major emergency departments of Pakistan from November 2010-March 2011. All the sites are tertiary care urban centers. All the patients who presented to the hospital's emergency department (ED) following a bomb blast injury as per self-report or the ambulance personnel were included in the study. Frequency of demographics, injury pattern, and outcomes were calculated. Results A total of 103 patients with bomb blast injuries presented to the selected emergency departments. The median age of patients was 30 years. Around three-fourth of the patients were males (n = 74, 74.7%). Most of the bomb blast patients were seen in Peshawar (n = 41, 39.8%) and Karachi city (n = 31, 30.1%) and the most common mode of arrival was non-ambulance transport (n = 71, 76.3%). Upper limb injuries (n = 12, 40%) were common in the under 18 age group and lower limb injuries (n = 31, 39.2%) in the 18 years and above group. There were a total of 8 (7.7%) deaths reported out of these 103 patients. Conclusion Bomb blast injuries in Pakistan generally affect young males. Non-ambulance transport is the most common way to access emergency departments (ED). Overall ED mortality is high and capturing data during a disaster in an emergency department is challenging.